Psychiatrists Report Praecox Feeling and Find It Reliable. A Cross-Cultural Comparison - Moskalewicz, Marcin; Kordel, Piotr; Brejwo, Agnieszka; Schwartz, Michael A.; Gozé, Tudi (Frontiers in Psychiatry, 2021)
Background: The psychopathological notion of the Praecox Feeling refers to an experience of strangeness and bizarreness that arises in a clinician during contact with a patient with schizophrenia. There is evidence that psychiatrists take advantage of this feeling in their diagnostic decisions despite the domination of an operationalized diagnostic approach. Methods: The article presents the results of a survey assessing the self-reported prevalence of the Praecox Feeling among psychiatrists in Poland and compares them with data from West Germany (1962), USA (1989), and France (2017) based on the same survey. Results: The study finds a consistent prevalence of reported feelings suggestive of the diagnosis of schizophrenia among psychiatrists of different cultural backgrounds and times. These feelings are independent of variables such as attitude towards schizophrenia, professional orientation, and professional experience and are considered reliable, even if not the most reliable, by the psychiatrists who have them. The study also finds that intersubjective phenomena, such as problematic affective attunement, gestures, and body language, are considered core to these feelings by the psychiatrists. Conclusions: The evidence confirms that psychiatrists' feelings about patients with schizophrenia are considered diagnostically relevant and calls for more deeply investigating the nature and diagnostic significance of these feelings. The article concludes with some speculations regarding the possible benefits of recognizing the Praecox Feeling in facilitating a psychotherapeutic encounter with psychotic patients.